Implementation of IT-Based Learning (E-Learning) In Growing Digital Literature in SMA Batik 1 Surakarta - Zumrida, Azza; Suwandi, Djoko; Karima, Mutiara (Universitas Muhammadiyah Surakarta, 2022)
The purpose of this study is to determine the application of e-learning as a means of increasing digital literacy at SMA Batik 1 Surakarta, as well as the value of e-learning and the barriers to its implementation. Interviews, interactive observation, and documentation were used to collect data in this qualitative descriptive research with a case study approach. Data analysis with a succession of operations employing flow or interactive approaches; data reduction, data display, conclusion drawing/verification. Source and technique triangulation strategies are used in triangulation. Conclusions of the research: 1) E-learning to replace offline learning that cannot be implemented due to the covid-19 pandemic at SMA Batik 1 Surakarta using teams office 365, LMS-based e-learning, and utilizing whatsapp and e-library as support; 2) Elearning to replace offline learning that cannot be implemented due to the covid-19 pandemic, thereby eliminating the fear of lost learning which will have an impact on lost generation; and 3) Availability of sufficient internet quota, weak network and learning motivation are obstacles to the implementation of e-learning at SMA Batik 1 Surakarta.